Feasible metabolisms in high pH springs of the Philippines - Cardace, Dawn; Meyer-Dombard, D'Arcy R.; Woycheese, Kristin M.; Arcilla, Carlo A. (Frontiers in Microbiology, 2015)
A field campaign targeting high pH springs in the Zambales and Palawan Ophiolites of the Philippines was conducted in 2012-2013, and enabled description of several springs sourced in altered pillow basalts, gabbros, and peridotites. We combine field observations of pH, temperature, conductivity, dissolved oxygen, and oxidation-reduction potential with analyses of major ions, dissolved inorganic carbon, dissolved organic carbon, and dissolved gas phases in order to model the activities of selected phases important to microbial metabolism, and to evaluate feasible metabolic reactions based on energy yield. We document changing geochemical inventories in these springs, and examine how the environment supports or prevents the function of certain microbial metabolisms.